Impact of Helminth Infection on Metabolic and Immune Homeostasis in Non-diabetic Obesity - Rajamanickam, Anuradha; Munisankar, Saravanan; Thiruvengadam, Kannan; Menon, Pradeep A.; Dolla, Chandrakumar; Nutman, Thomas B.; Babu, Subash (Frontiers in Immunology, 2020)
Several epidemiological and immunological studies indicate an inverse relationship between obesity / metabolic syndrome and helminth infections. Numerous studies demonstrated that obesity is concomitant with chronic low-grade inflammation which is characterized by vital changes in cellular composition and function of adipose tissue. However, the impact of helminth infection on the homeostatic milieu in obesity is not well understood. To determine the relationship between Strongyloides stercoralis (Ss) infection and obesity, we examined an array of parameters linked with obesity both before and at 6 months following anthelmintic treatment. To this end, we measured serum levels of pancreatic hormones, incretins, adipokines and Type-1, Type-2, Type-17 and other proinflammatory cytokines in those with non-diabetic obesity with (INF) or without Ss infection (UN). In INF individuals, we evaluated the levels of these parameters at 6 months following anthelmintic treatment. INF individuals revealed significantly lower levels of insulin, glucagon, C-peptide, and GLP-1 and significantly elevated levels of GIP compared to UN individuals. INF individuals also showed significantly lower levels of Type-1, Type-17 and other pro-inflammatory cytokines and significantly increased levels of Type-2 and regulatory cytokines in comparison to UN individuals. Most of these changes were significantly reversed following anthelmintic treatment. Ss infection is associated with a significant alteration of pancreatic hormones, incretins, adipokines and cytokines in obese individuals and its partial reversal following anthelmintic treatment. Our data offer a possible biological mechanism for the protective effect of Ss infection on obesity.